Political economy and information capitalism in India: digital divide, development and equity - Parayil, Govindan (ed.) (New York, 2006)
Recent advances in information and communications technologies or ICTs seemed to have opened up new opportunities for India as a major exporter of software and information technology-enabled services (ITES), thanks to globalisation and liberalisation of the domestic economy. This export boom has spurred renewed hopes and expectations in India and rekindled hopes of creating large-scale employment opportunities and economic transformation. However, despite the dynamism of its software and ITES sectors and the rhetorical flourishes of industry leaders and politicians, India needs to do a lot more to bring the benefits of ICTs to the hundreds of millions still eking out a living on less than a dollar a day, rather than let the ICT revolution benefit just the hundreds of thousands with the right skills and access. This theoretically and empirically engaging volume takes stock of the larger impact and implications of the ICT revolution on Indian economy and society; specifically, it reflects on and analyses the political economy of informational development in India.
Keywords: Information technology-Economic aspects